Mengembalikan Citra Pendidikan Dalam Bingkai Moderasi Beragama Ditinjau Dari Perspektif Pendidikan Agama Kristen - Putra Wijalin Halwa; Emanuel Kristinus Ndruru; Yeremia Hia (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Religious moderation education is often used in both formal and informal educational institutions. In fact, religious moderation has developed significantly in learning practices. Several studies on the implementation and growth of religious moderation education in educational institutions found that the concept of religious moderation can awaken students' understanding of how to behave and how to behave in moderation. The author uses a qualitative research method with a descriptive approach, where this method looks at the data collected as the key to research. Religious moderation education is often used in both formal and informal educational institutions. In fact, religious moderation has developed significantly in learning practices. Several studies on the implementation and growth of religious moderation education in educational institutions found that the concept of religious moderation can awaken students' understanding of how to behave and how to behave in moderation. The purpose of writing an article on Educational Restoration in the Frame of Religious Moderation from the perspective of Christian religious education is to discuss the importance of educational restoration using a religious moderation approach in the context of Christian religious education